Kinetic studies of CO2 methanation over a Ni/γ-Al2O3 catalyst using a batch reactor. (17th February 2016) - Yang Lim, Jin; McGregor, J.; Sederman, A.J.; Dennis, J.S.
Abstract: The methanation of CO2 was investigated over a wide range of partial pressures of products and reactants using a gradientless, spinning-basket reactor operated in batch mode. The rate and selectivity of CO2 methanation, using a 12 wt% Ni/ γ –Al2 O3 catalyst, were explored at temperatures 453–483 K and pressures up to 20 bar. The rate was found to increase with increasing partial pressures of H2 and CO2 when the partial pressures of these reactants were low; however, the rate of reaction was found to be insensitive to changes in the partial pressures of H2 and CO2 when their partial pressures were high. A convenient method of determining the effect of H2 O on the rate of reaction was also developed using the batch reactor and the inhibitory effect of H2 O on CO2 methanation was quantified. The kinetic measurements were compared with a mathematical model of the reactor, in which different kinetic expressions were explored. The kinetics of the reaction were found to be consistent with a mechanism in which adsorbed CO2 dissociated to adsorbed CO and O on the surface of the catalyst with the rate-limiting step being the subsequent dissociation of adsorbed CO. Highlights: CO2 methanation investigated in a spinning-basket reactor operated in batch. Rate and selectivity determined for 12 wt% Ni/ γ Al2 O3 catalyst, 453–483 K to 20 bar. Convenient method of determining the effect of H2 O on the rate was developed. Kinetics were consistent with adsorbed CO2 dissociating to adsorbed CO and O. The RDS is the subsequent dissociation of adsorbed CO.